Development of a fixed-wing Unmanned Aerial Vehicle (UAV) - Poh, Teck Keng. (2013)
In aviation, the deployment of unmanned technology in aircraft, or the Unmanned Aerial Vehicle (UAV) has proven its worthiness in both military and commercial purposes. In addition to basic aviation, more technological capabilities were explored and researched to maximise the advantage of unmanned flying.